Electronic structure regulation of an ultra-thin MOF-derived NiSe2/NiS2@NC heterojunction for promoting the hydrogen evolution reaction. Issue 4 (24th January 2022) - Lu, Kebin; Sun, Jianpeng; Xu, Huakai; Jiang, Chuanhai; Jiang, Weifeng; Dai, Fangna; Wang, Hong; Hao, Hongguo
Abstract : A Ni-MOF is used as a precursor to synthesize a NiSe2 /NiS2 @NC heterojunction with rich phase interfaces through a selenization/sulfurization process. Overpotentials of 188 mV and 211 mV are achieved in acidic and alkaline media at 10 mA cm −2 . Abstract : Transition metal selenides (TMSes) are considered promising electrocatalysts for the hydrogen evolution reaction (HER) due to their narrow bandgap, unique morphology and low cost. Herein, using a metal–organic framework (MOF) as a precursor, a NiSe2 /NiS2 @NC electrocatalyst with abundant heterogeneous interfaces was designed and synthesized through a simultaneous selenization/sulfurization process. The heterojunction could provide more catalytic sites, accelerate the transfer of ions/gas, and optimize the electronic structure of the interface, and then exhibit overpotentials of 188 mV and 211 mV at 10 mA cm −2 in acidic and alkaline media. The density functional theory (DFT) calculation results showed that the heterogeneous interface can optimize the electronic structure. Meanwhile, the Gibbs free-energy for H* adsorption was reduced to −0.35 eV, which means that the interface can effectively accelerate the HER kinetics. This work provides a strategy for constructing heterojunction electrocatalysts and understanding the role of electronic structure in the HER.